KREDIT SINDIKASI SEBAGAI ALTERNATIF PEMBIAYAAN KREDIT DALAM SKALA BESAR - Endraswari, A.A. Mirah; Sudantra, I Ketut (Kertha Wicara : Journal Ilmu Hukum; Vol.2, No.1 Edisi Februari 2013)
Bank financial institusions is an entity that has a very important role both in the field of industry, services, trade and the other fields. The increasing development of the times, affect the credit demand. Given the limitations of a bank to provide a loan to the debtor is called the legal lending limit, causing the bank is not able to meet the demand for very high credit. But now, with the presence of sydicated loans, loan demand remains on a large scale can be provided by the bank without violating the provisions of the legal lending limit.
Keywords: Credit, Syndicated loan, financing, Legal lending limit